2023
DOI: 10.5194/gmd-16-4427-2023
|View full text |Cite
|
Sign up to set email alerts
|

The three-dimensional structure of fronts in mid-latitude weather systems in numerical weather prediction models

Abstract: Abstract. Atmospheric fronts are a widely used conceptual model in meteorology, most encountered as two-dimensional (2-D) front lines on surface analysis charts. The three-dimensional (3-D) dynamical structure of fronts has been studied in the literature by means of “standard” 2-D maps and cross-sections and is commonly sketched in 3-D illustrations of idealized weather systems in atmospheric science textbooks. However, only recently has the feasibility of the objective detection and visual analysis of 3-D fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…Finally, improving the homogeneity, temporal resolution, and accuracy of the upper air temperature records is imperative to make them appropriate for weather forecasting, atmospheric boundary layer, and climate change studies. Significant progress has been made to enhance upper air temperature records acquired utilizing in situ and satellite-based instruments to improve weather forecasting [171], the understanding of atmospheric boundary layer processes [172], and climate change studies [140]. Studies have demonstrated that RSs are still by far the most effective tools for in situ atmospheric temperature observations, but operational meteorological satellites are gradually closing the gap despite their reliance on in situ data for their calibration and validation [77,146,151].…”
Section: Challenges Of Using In Situ Radiosondes and Satellites For U...mentioning
confidence: 99%
“…Finally, improving the homogeneity, temporal resolution, and accuracy of the upper air temperature records is imperative to make them appropriate for weather forecasting, atmospheric boundary layer, and climate change studies. Significant progress has been made to enhance upper air temperature records acquired utilizing in situ and satellite-based instruments to improve weather forecasting [171], the understanding of atmospheric boundary layer processes [172], and climate change studies [140]. Studies have demonstrated that RSs are still by far the most effective tools for in situ atmospheric temperature observations, but operational meteorological satellites are gradually closing the gap despite their reliance on in situ data for their calibration and validation [77,146,151].…”
Section: Challenges Of Using In Situ Radiosondes and Satellites For U...mentioning
confidence: 99%
“…The automated detection and tracking of 2-D and 3-D atmospheric features including cyclones, fronts, jet streams, or atmospheric rivers (ARs) in simulation and observation data has multiple applications in meteorology. For example, automatically detected features are used for weather forecasting (e.g., Hewson and Titley, 2010;Mittermaier et al, 2016;Hengstebeck et al, 2018), statistical and climatological studies (e.g., Dawe and Austin, 2012, Pena-Ortiz et al, 2013, Schemm et al, 2015, Sprenger et al, 2017, Lawrence and Manney, 2018, and visual data analysis (e.g., Rautenhaus et al, 2018;Bösiger et al, 2022;Beckert et al 2023). Features are typically objectively detected based on a set of physical and mathematical rules.…”
Section: Introductionmentioning
confidence: 99%
“…Features are typically objectively detected based on a set of physical and mathematical rules. For example, cyclones can be identified by means of searching for minima or maxima in variables including mean sea level pressure and lower-tropospheric vorticity (Neu et al, 2013;Bourdin et al 2022), atmospheric fronts by means of derivatives of a thermal variable combined with threshold-based filters (Jenkner et al, 2010;Hewson and Titley, 2010;Beckert et al, 2023), and ARs based on thresholding and geometric requirements (Guan and Waliser, 2015;Shields et al, 2018).…”
Section: Introductionmentioning
confidence: 99%